Rompimento da barragem de mineração em Brumadinho/MG: Vivências e trajetórias ocupacionais de idosos em um contexto de desastre - Marcelo Brandão de Souza (2023)
Introduction: Disaster occurrences have become more frequent in recent years, resulting in severe consequences for human lives, the environment, the economy, and society as a whole. This has become a growing concern for public administrators, researchers, and healthcare professionals. Populations and communities affected by disasters may undergo critical and significant changes in their lives, including restrictions on important and necessary occupations for daily living. This context is particularly worrisome for the elderly, who are among the most vulnerable groups in disaster situations. Objective: To understand the experiences and occupational trajectories of elderly individuals who experienced the mining dam collapse disaster in Brumadinho/MG in 2019. Method: An exploratory study with a cross-sectional design using thematic oral history as a data collection method. The sample selection was convenience-based, using the snowball sampling technique, with key informants facilitating the formation of specific participant profiles. Seventeen interviews were conducted individually with elderly participants, with an average age of 72, residing in Brumadinho, Minas Gerais (MG). All interviews were recorded and transcribed with participants' permission. MAXQDA software was used for data storage, organization, and coding. Data analysis employed content analysis, using thematic units to objectively and concisely describe the interview content. The process concluded with triangulation as a validation strategy for acquired information. Results: Analysis of the elderly participants' narratives allowed the construction of two categories, each with four subcategories: 1) Re-living the disaster: A) Memories and Feelings, B) Memories of Those Who Passed Away, C) Spirituality, D) Anger Towards the Company. 2) Changes in Daily Life and Well-being: A) Effects on Physical and Mental Health, B) Disruptions in Occupations After the Collapse, C) Restrictions on Social Interaction and Personal Relationships, D) Reframing Occupations After the Collapse. The elderly recalled memories of the disaster, mourned the losses of their beloved ones, sought mental and emotional balance through spirituality, and expressed feelings of anger and rage toward the company responsible for the dam. Due to the experienced stress, there were changes in the elderly's health and compromised mental well-being. Pre-collapse routine activities focused on domestic life, work, and meaningful activities. There were changes in daily activities, particularly in leisure, such as reduced participation in public places, restricted social interaction with friends and family, and altered schedules for leaving home. Despite facing such a challenging moment in their lives, the elderly demonstrated the ability to rebuild and rediscover their lives through meaningful activities, fostering a sense of well-being. Conclusion: Emphases on the need for disaster-specific public policies targeting the elderly, as this area is still underdeveloped nationally, and the elderly belong to the most vulnerable group. It is expected that the evidence obtained from this research provides scientific support for Occupational Therapy, further strengthening human occupation as a coping strategy for populations affected by disasters, contributing to health and well-being promotion.